Conceptual Framework about Tokenism Phenomenon in Organizations - SÜRGEVİL DALKILIÇ, Olca; KURT YILMAZ, Benan (International Journal of Contemporary Economics and Administrative Sciences, 2019)
In this study, it is aimed to introduce and examine the tokenism phenomenon. Kanter (1977) argued tokenism as an “artificial appearance” achieved by including a limited number of individuals in the minority group in effective positions within the existing group due to their characteristics (gender, race, religion, age, etc.) accepted as disadvantage or groups’ characteristics different from the dominant group. In this context, tokenism is examined conceptually and then the group typologies serving to the tokenism are stated on the basis of proportional distributions. Then dimensions of restrictions and limitations applied by the dominant group to the tokens are addressed, and socio-psychological approaches supporting and providing a basis for the theory of tokenism are explained.